64.2k views
0 votes
What is the product? (–3s + 2t)(4s – t)

User CleanX
by
5.2k points

2 Answers

3 votes

Answer: -12s^2 + 11st -2t^2

Explanation:

= (-3s + 2t)(4s - t)

= -12s^2 + 3st + 8st -2t^2

= -12s^2 + 11st -2t^2

Answer Provided by GauthMath please heart and comment thanks if you like.

4 votes

Answer:


- 12 {s}^(2) + 11st - 2 {t}^(2)

Explanation:

(–3s + 2t)(4s – t)

= -3s (4s - t) + 2t(4s - t)


= - 12 {s}^(2) + 3st + 8st - 2 {t}^(2)


= - 12 {s}^(2) + 11st - 2 {t}^(2) (ans)

User Yonlif
by
5.3k points